Total talus metallosis with ankle arthroplasty - Thomas Milisits, DPM, MPH; John Ellis Marshall, IV, DPM; Michael Siciliano, DPM; Justin Garvin, DPM; Jason Miller, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases)
Total ankle total talus replacement (TATTR) is gaining popularity in the foot and ankle surgery world in patients with end-stage ankle arthritis with concomitant pathology to the talus. What we typically do not consider is metal hypersensitivity when it comes to these complex reconstructive procedures with a substantial amount of hardware. Future research should aim to gain a greater understanding of metal components in varying company materials to determine compatibility. We report a case of a healthy 62-year-old female who underwent TAR with numerous complications and revisions ultimately leading to a TATTR and suspected hypersensitivity reaction.